2021
DOI: 10.1007/s11156-021-00991-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity and earnings management: the case of female directors with financial background

Abstract: Past evidence generally suggests that the presence of female directors on corporate boards tends to improve earnings quality due to these directors’ superior monitoring abilities. However, it is not clear which characteristics and skills of female directors drive such abilities. In this paper, we focus on the financial background of female directors, an area which remains largely unexplored in existing literature. The results show that the participation of female directors with relevant financial background im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(61 citation statements)
references
References 91 publications
1
53
0
7
Order By: Relevance
“…Composition of the board is considered to be one of the CG attributes that ensure the existence of appropriate balance of power on the board, for the reason that the dominance of an individual or a group of individuals in the board decision making process can be avoided (Zalata et al, 2021). Boards are considered to be effective and independent, when most of the directors on boards are outside independent directors, when outside independent directors do not share major family relationships, professional services, financial relationships, employment, and interlocked directorships with the management team (Ayuso & Argandoña, 2009; Shivdasani & Zenner, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Composition of the board is considered to be one of the CG attributes that ensure the existence of appropriate balance of power on the board, for the reason that the dominance of an individual or a group of individuals in the board decision making process can be avoided (Zalata et al, 2021). Boards are considered to be effective and independent, when most of the directors on boards are outside independent directors, when outside independent directors do not share major family relationships, professional services, financial relationships, employment, and interlocked directorships with the management team (Ayuso & Argandoña, 2009; Shivdasani & Zenner, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies pointed out that female directors' presence on the board consolidates their efficiency and effectiveness (Zalata et al, 2019(Zalata et al, , 2022. Women are assumed to be more ethically minded than their male counterparts and are expected to abstain from unethical activities such as EM (Komal et al, 2021;Nekhili et al, 2022).…”
Section: Board Gender Diversitymentioning
confidence: 99%
“…Some studies found a positive association between gender diversity in the audit committee on the quality of financial reports (e.g., Gul et al, 2007;Wahid, 2019). In contrast, some studies have found that women members in the audit committee negatively affect financial reports' quality (e.g., Ud Din et al, 2021;Zalata, 2022).…”
Section: -Audit Committee Members' Gender Diversitymentioning
confidence: 99%